Ethical Politic in the View of Bediuzzaman Said Nursi: A Response to Political Pragmatism - Pramono, Muhamad Fajar; Latief, Mohamad; Widodo, Chandra Dwisetyo (IAIN Ponorogo, 2024)
This article discusses political ethics according to Badiuzzaman Said Nursi as a response to political pragmatism. This research departs from the rampant cases that reflect the pragmatic attitude of political elites. They prioritise profits and benefits over values and rules resulting in abuse of authority. This is due to the political elite leaving religious values as the basis of political ethics. Said Nursi has an interesting concept to answer the problem of political pragmatism. Nursi offers political ethics based on Islamic values. The findings of this article reveal that Said Nursi's political ethics are based on six basic principles including tawhid, consultation, freedom, justice, equality and nationalism. For Nursi, politics must be based on religion as a moral force that can control human desires and passions, religion becomes a solid foundation for creating prosperity and stability of the state. Thus, the purpose of politics is not self-satisfaction but to achieve the pleasure of Allah SWT and realise the benefit of the people. This research is a qualitative study with a critical analysis method uses Risale-i Nur as the primary reference and secondary in the form of related scientific works.